Cladribine: mechanisms and mysteries in multiple sclerosis. Issue 12 (10th July 2018) - Jacobs, Benjamin Meir; Ammoscato, Francesca; Giovannoni, Gavin; Baker, David; Schmierer, Klaus
Abstract : Objectives: The aims of this manuscript were to review the evidence for the efficacy and safety of cladribine in multiple sclerosis (MS) and to review the molecular and cellular mechanisms by which cladribine acts as a disease-modifying therapy in MS. Methods: This is a narrative review of the available clinical and preclinical data on the use of cladribine in MS. Results: Clinical trial data argue strongly that cladribine is a safe and effective therapy for relapsing MS and that it may also be beneficial in progressive MS. The pharmacology of cladribine explains how it is selectively toxic towards lymphocytes. Immunophenotyping studies show that cladribine depletes lymphocyte populations in vivo with a predilection for B cells. In vitro studies demonstrate that cladribine also exerts immunomodulatory influences over innate and adaptive immunity. Conclusions: Cladribine is a safe and effective form of induction therapy for relapsing MS. Its mechanism of benefit is not fully understood but the most striking action is selective, long-lasting, depletion of B lymphocytes with a particular predilection for memory B cells. The in vivo relevance of its other immunomodulatory actions is unknown. The hypothesis that cladribine's action of benefit is to deplete memory B cells is important: if correct, it implies that selective targeting of this cell population and sparing of other lymphocytes could modify disease activity without predisposing to immunosuppression-related complications.